Վան քաղաքի արհեստները - Գասպարեան, Նազանի (տպ. Atlas)
Based on a set of data and information on the development of crafts in the city of Van and its various directions, the study depicts a panoramic picture of the crafts in the city and concludes that craft work had a competitive edge and was in high demand not only in the city and its environs but even in Constantinople. The study notes that the crafts constituted a rich, valuable part of the cultural heritage of the Armenians in Van. Dozens of crafts were developed in Van and a number of workshops were opened during the second half of the 19th century. In particular, ironwork, furniture making, tailoring, and shoemaking were well-developed crafts. The products of jewelers and silversmiths were works of art and were very famous not only in the country but also abroad. During World War I Van was ethnically cleansed of its indigenous Armenians. They were uprooted and deported to Iran, Eastern Armenia and Georgia. However, Van master craftsmen continued to work and create in their new homelands.
Keywords: Արհեստագործութիւն